1996
DOI: 10.1002/art.1780391209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sulfasalazine and placebo in the treatment of ankylosing spondylitis. A department of veterans affairs cooperative study

Abstract: Objective. To determine whether sulfasalazine (SSZ) at a dosage of 2,000 mg/day is effective for the treatment of active ankylosing spondylitis (AS) that is not controlled with nonsteroidal antiinflammatory drug therapy.Methods. Two hundred sixty-four patients with AS were recruited from 15 clinics, randomized (doubleblind) to SSZ or placebo treatment, and followed up for 36 weeks. Treatment response was based on morning stiffness, back pain, and physician and patient global assessments.Results. While longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(73 citation statements)
references
References 16 publications
2
66
0
5
Order By: Relevance
“…Patient self-assessment measures included morning stiffness, night pain, patient global assessment, and Spondylitis Functional Index, as described in the article on SSZ in ankylosing spondylitis, which appears elsewhere in this issue of Arthritis and Rheumatism (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient self-assessment measures included morning stiffness, night pain, patient global assessment, and Spondylitis Functional Index, as described in the article on SSZ in ankylosing spondylitis, which appears elsewhere in this issue of Arthritis and Rheumatism (9).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the analytic methods appears elsewhere in this issue ofArthritis and Rheumatism (9). Briefly, the change in primary and secondary outcome measures from baseline to the last available followup were analyzed using t-tests for continuous data and chi-square tests for ordinal and categorical data.…”
Section: Methodsmentioning
confidence: 99%
“…At least ten double-blind studies have evaluated the efficacy of sulfasalazine, but none included patients with IBD arthropathies. A meta-analysis of five randomized controlled studies in 1990 concluded that there are some beneficial effects of sulfasalazine therapy [22] in AS, but this was followed by two large multicenter trials showing that efficacy of this treatment was limited to the peripheral joint involvement of the disease [23,24,25]. While less well evaluated, the use of mesalamine is supported by the results of two small studies [21, 26, 27].…”
Section: Treatmentmentioning
confidence: 99%
“…(UCSF) index 14,15 , and the Berlin index 10 . However, there is no consensus or a clear recommendation regarding which of these enthesitis indices should be used, especially in pSpA 16,17 .…”
mentioning
confidence: 99%